Multiple Densities of the Chronic Subdural Hematoma in CT Scans - Park, Hye-Ran (The Korean Neurosurgical Society, 2013)
OBJECTIVE: Density of the chronic subdural hematoma (cSDH) is variable. It often appears to be mixed density. Multiple densities of cSDH may result from multiple episodes of trauma. We investigated the frequency of mixed density and the causes of head injuries representing each density. METHODS: We could collect 242 cases of chronic SDH. The cSDHs were classified into four groups; hypodensity, homogeneous isodensity, layered type, and mixed type on the basis of CT scans. RESULTS: The density of cSDH was isodense in 115 patients, hypodense in 31 patients, mixed in 79 cases, and layered in 17 cases. The cSDH was on the left side in 115 patients, on the right side in 70 patients, and bilateral in 40 patients. The history of trauma was identifiable in 122 patients. The etiology could be identified in 67.7% of the hypodense hematomas, while it was obscure in 59.5% of the mixed hematomas. CONCLUSION: Mixed density of cSDH results from multiple episodes of trauma, usually in the aged. It is hard to remember all the trivial traumas for the patients with the mixed density cSDHs. Although there were membranes within the mixed density hematomas, burr-holes were usually enough to drain the hematomas.